PERAN DAN PENGUATAN KEGIATAN LITERASI DIGITAL DI SEKOLAH MELALUI PROGRAM “GOES TO SCHOOL” - Septiawan, Yudi; Alkodri, Ari Amir; Supardi, Supardi; Ilham, Ilham; Safitri, Linda; Amanda, Reffi (Universitas Negeri Medan, 2024)
In the current digital era, the role and strengthening of literacy at the high school and equivalent levels is significant. It aims to ensure that students receive assistance and learn about the development of this technology. Teenagers are required to use technology not only well but also appropriately. 'Goes to School' Literacy Strengthening Activity is one way for students to understand what information is appropriate to share and pass on to the community through various media. Of the four schools visited at SMK Negeri 1 Pangkalpinang, SMK Negeri 1 Simpang Katis, SMK Negeri 1 Sungailiat, and SMK Negeri 1 Simpang Rimba, the team found that almost all students use Android and nearly all students use social media in their daily lives. However, quite a few of them need help understanding the good and wise use of social media. Through this literacy-strengthening activity, the team also invited high school and vocational school students to intensify the importance of literacy in various media, including participating in Literacy School activities.